Expression and role of a2 vacuolar-ATPase (a2V) in trafficking of human neutrophil granules and exocytosis. Issue 6 (15th April 2015) - Gilman-Sachs, Alice; Tikoo, Anjali; Akman-Anderson, Leyla; Jaiswal, Mukesh; Ntrivalas, Evangelos; Beaman, Kenneth
Abstract : The a2 isoform of V-ATPase on neutrophil granule membranes decreases intragranular pH as the cytoplasmic pH becomes acidic after stimulation, facilitates exocytosis, and translocates to the cell surface. Abstract: Neutrophils kill microorganisms by inducing exocytosis of granules with antibacterial properties. Four isoforms of the "a" subunit of V-ATPase—a1V, a2V, a3V, and a4V—have been identified. a2V is expressed in white blood cells, that is, on the surface of monocytes or activated lymphocytes. Neutrophil associated-a2V was found on membranes of primary (azurophilic) granules and less often on secondary (specific) granules, tertiary (gelatinase granules), and secretory vesicles. However, it was not found on the surface of resting neutrophils. Following stimulation of neutrophils, primary granules containing a2V as well as CD63 translocated to the surface of the cell because of exocytosis. a2V was also found on the cell surface when the neutrophils were incubated in ammonium chloride buffer (pH 7.4) a weak base. The intracellular pH (cytosol) became alkaline within 5 min after stimulation, and the pH increased from 7.2 to 7.8; this pH change correlated with intragranular acidification of the neutrophil granules. Upon translocation and exocytosis, a2V on the membrane of primary granules remained on the cell surface, but myeloperoxidase was secreted. V-ATPase may have a role in the fusion of the granule membrane with the cell surface membrane before exocytosis. These findings suggest that the granule-associated a2V isoform has a role in maintaining a pH gradient within the cell between the cytosol and granules in neutrophils and also in fusion between the surface and the granules before exocytosis. Because a2V is not found on the surface of resting neutrophils, surface a2V may be useful as a biomarker for activated neutrophils.